PERANCANGAN PRODUK TEMPAT TISU MULTIFUNGSI DENGAN MENGGUNAKAN QUALITY FUNCTION DEPLOYMENT (QFD) - Siregar, Ikhsan; Adhinata, Kevin (Jurnal Sistem Teknik Industri, 2017)
Changes in human mindset along with the development of technology, trends and the need for quality products increasingly require the development of more complex product functions to meet the expectations and needs of consumers as users of the product. Merging several functions in a single product is often become the main focus for managers in research and product development departments to produce product design concepts in the present. The success of a product can be measured by how much the existence of the product can be accepted by the consumer so as to increase profit for the company or producer. Product design is an idea, concept development, testing that done before the production process of an object or product is done. The product designer evaluates the ideas and realizes them through the product. The design of products to be made in this research is multifunctional tissue box. Ideas for product design are obtained through brainstorming. The next step is to make a questionnaire based on the results of brainstorming to obtain information and know the consumer requirement for the product. In designing the tissue box, clarifying objectives is done in the form of objective trees and the functional analysis in the form of block diagrams. Then Quality Function Deployment is done to improve product quality based on consumer needs. Alternative generation with Morphological Chart is done to achieve solutions to product design problems. There were 4 alternatives with relative importance value for alternative 1 = 4.8719; alternative 2 = 3.7723; alternative 3 = 3.4941 and alternative 4 = 2.8785. The next step is to do value engineering on the product through improving details to increase the value of the product and decrease the production cost. The cost incurred in making the product before improving details is Rp 152.352, - while the cost incurred after improving details is Rp. 130602, -